2005
DOI: 10.1007/s11071-005-1921-1
|View full text |Cite
|
Sign up to set email alerts
|

A Reduced Order Cyclic Method for Computation of Limit Cycles

Abstract: A reduced order cyclic method was developed to compute limit-cycle oscillations for large, nonlinear, multidisciplinary systems of equations. Method efficacy was demonstrated for two simplified models: a typical-section airfoil with nonlinear structural coupling and a nonlinear panel in high-speed flow. The cyclic method was verified to maintain second-order temporal accuracy, yield converged limit cycles in about 10 Newton iterates, and provide precise estimates of cycle frequency. This method was projected o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In order to find the amplitudes and periods of the limit cycles excited by the fluid flow over the plate, a cyclic method similar to [70,71] is employed. In this method, the modal amplitudes α n and period of vibration for the system T are sought such that…”
Section: Fluid-structure Interactionmentioning
confidence: 99%
“…In order to find the amplitudes and periods of the limit cycles excited by the fluid flow over the plate, a cyclic method similar to [70,71] is employed. In this method, the modal amplitudes α n and period of vibration for the system T are sought such that…”
Section: Fluid-structure Interactionmentioning
confidence: 99%
“…The cyclic method in combination with the finite difference method for the time discretization has been described in previous work. 1 The cyclic method will again be described here for clarity. Two other computational techniques, the Time Spectral method and the Spectral Element method will be used in conjunction with the cyclic method in place of the finite difference discretization.…”
Section: Formulationmentioning
confidence: 99%
“…Two studies have been identified in the literature. Prediction of a subcritical LCO has been investigated using a reduced-order cyclic method for a pitch-plunge aerofoil in incompressible flow [4,13]. The method combines the techniques of proper orthogonal decomposition and computation of LCO in the modal subspace using an orbital approach and allows for the direct computation of LCO.…”
Section: Introductionmentioning
confidence: 99%